If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + -10y + -1y = 9 Combine like terms: 12y + -10y = 2y 2y + -1y = 9 Combine like terms: 2y + -1y = 1y 1y = 9 Solving 1y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '1'. y = 9 Simplifying y = 9
| -6(3n-4)=-9n-30 | | (x+y)(xy-1)=0 | | 374=m/23 | | 2/3m-4=12 | | x^2+y^2-4X-6Y+17=0 | | -3/5-2/ | | 13y-7y+y+4y-8y=12 | | 6y+2=4y+12 | | 4(-4+2b)-8(6b-7)=80 | | -1/2*0-2 | | -6(1+n)+4(3n+4)=58 | | (x)=7x^2+2x | | -2(3x+6)=20-4x | | 11p-p-8p-p=19 | | -5(4b-6)-2(5b-2)=4 | | 9h+3=5h | | 30x/(x^3) | | 15z-14z=20 | | -4+20-6-(-18)+(-11)= | | -84+10x=3x+63 | | 3/4--16 | | -5x-15=50 | | -2c+30=24 | | -4+20-6(-18)+(-11)= | | 14z-13z=5 | | -10m+2=-8m-8 | | 13d-12d=1 | | -6x+y = -3 | | x/7-1=-6 | | 230/30=345/x | | M/5=175.3 | | -5/6x-1/9x=-102 |